Uji Kadar Hambat Minimum Ekstrak Etanol Buah Asam Jawa (Tamarindus indica L.) Muda Pada Bakteri Staphylococcus aureus Penyebab Diare - Nurhikmah Nurhikmah; Dwi Kartika Risfianty; Irna Il Sanuriza; Khaerul Ihwan; Baiq Naili Dewi Atika; Irfan Jayadi; Pahmi Husain (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2023)
Tamarind (Tamarindus indica L.) can cure various diseases, one of which is diarrheal disease caused by Staphylococcus aureus bacteria. Tamarind fruit contains tannin compounds that have antibacterial abilities. This study aims to determine the inhibitory power of ethanol extract of young tamarind fruit against Staphylococcus aureus bacteria that cause diarrhea. The concentrations used in this study were 10%, 25%, 45%, 75% and 100%. The method used is the well diffusion method with 4 treatments and 4 repeats. The results showed that ethanol extracts of tamarind fruit young proved to be able to suppress the growth of Staphylococcus aureus bacteria with the highest inhibitory zone of 19.85 mm. This inhibitory power is a strong category in inhibiting bacterial growth.